2015
DOI: 10.1186/s40294-015-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

A Gaussian function model for simulation of complex environmental sensing

Abstract: FindingsWireless sensors are a growing area of research focus. In previous works Niazi and Hussain (2011a, b), a formal model of wireless sensor networks has been given along with an agent-based simulation model. The idea was to use sensing to examine and identify complex behavior such as flocking. The papers also presented a formal specification model is based on the Z formal specification language. While the idea was interesting, these papers did not present a traditional mathematical model. In the current p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The use of the double Hill function was motivated by myocyte recruitment during preload, which is fundamentally a cooperative process 28 and consequently, is modeled by a sigmoidal Hill function 29 . Both the Gaussian function and Boltzmann distribution not only gave sub-par results compared to the Hill model, but also did not model the myocyte recruitment mechanism: The Gaussian function is symmetric about a mean 23 , which is not correct for our model because contraction and relaxation are not symmetric processes [30][31][32][33][34][35][36][37][38][39] . The Boltzmann distribution is a probability distribution of physical states 25 , and hence does not capture the dynamic cooperativity of myocytes recruitment.…”
Section: Lumped Parameter Modelmentioning
confidence: 99%
“…The use of the double Hill function was motivated by myocyte recruitment during preload, which is fundamentally a cooperative process 28 and consequently, is modeled by a sigmoidal Hill function 29 . Both the Gaussian function and Boltzmann distribution not only gave sub-par results compared to the Hill model, but also did not model the myocyte recruitment mechanism: The Gaussian function is symmetric about a mean 23 , which is not correct for our model because contraction and relaxation are not symmetric processes [30][31][32][33][34][35][36][37][38][39] . The Boltzmann distribution is a probability distribution of physical states 25 , and hence does not capture the dynamic cooperativity of myocytes recruitment.…”
Section: Lumped Parameter Modelmentioning
confidence: 99%
“…where, P LV (t), V(t), and V 0 are the LV time-varying pressure, time-varying volume, and unloaded volume, respectively (Keshavarz-Motamed et al, 2016). As explained by Keshavarz-Motamed (2020), to represent the normalized elastance function of the LV, we observed that among summation of Gaussian functions (Pironet et al, 2013;Chaudhry, 2015), Boltzmann Distribution (McDowell, 1999), double Hill function (Mynard et al, 2012;BroomĂ© et al, 2013), and the latter provided the most physiologically accurate results (e.g., pressure, volume, and flow waveforms). The double Hill function which is a cooperative process (Moss et al, 2004), as physiologically expected from myocyte recruitment during preload and is modeled by a sigmoidal Hill function.…”
Section: Left Ventriclementioning
confidence: 93%
“…There have been attempts for quantifying hemodynamics and for fundamental understanding of cardiovascular mechanics using lumped parameter modeling (Segers et al, 2003;Geven et al, 2004;TannĂ© et al, 2008;Garcia et al, 2009Garcia et al, , 2005Keshavarz-Motamed et al, 2011, 2015Mynard et al, 2012;BroomĂ© et al, 2013;de Canete et al, 2013;Revie et al, 2013;Benevento et al, 2015;Frolov et al, 2016;Mihalef et al, 2017;Duanmu et al, 2018;Li et al, 2018;Pant et al, 2018;Ben-Assa et al, 2019;Mao et al, 2019;Keshavarz-Motamed, 2020;Keshavarz-Motamed et al, 2020). All of these models [except (Keshavarz-Motamed et al, 2016;Keshavarz-Motamed, 2020)] cannot satisfy Requirements #1 and #2 above, although they were very important to provide fundamental understandings using idealized or hypothetical cases (Segers et al, 2003;Geven et al, 2004;TannĂ© et al, 2008;Garcia et al, 2009Garcia et al, , 2005Keshavarz-Motamed et al, 2011, 2015Mynard et al, 2012;BroomĂ© et al, 2013;de Canete et al, 2013;Revie et al, 2013;Benevento et al, 2015;Frolov et al, 2016;Mihalef et al, 2017;Duanmu et al, 2018;…”
Section: Introductionmentioning
confidence: 99%
“…A formal model of wireless sensor networks in combination with agent-based simulation model is presented in (Niazi and Hussain 2011a, b). As this work lacks mathematical modelling that is why it is extended in (Chaudhry 2015) using Gaussian function for sensing of emergent behaviour in CAS. Experiments have been carried out to deduce centrality metrics effects to validate the roles of nodes in complex networks ).…”
Section: Literature Review Of Cas Using Formal Methodsmentioning
confidence: 99%